2021
DOI: 10.1016/j.cophys.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and COVID-19

Abstract: In people recovering from COVID-19, there is concern regarding potential long-term pulmonary sequelae and associated impairment of functional capacity. Data published thus far indicate that spirometric indices appear to be generally well preserved, but that a defect in diffusing capacity (DLco) is a prevalent abnormality identified on follow-up lung function; present in 20-30% of those with mild to moderate disease and 60% in those with severe disease. Reductions in total lung capacity were commonly reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 32 publications
2
40
1
2
Order By: Relevance
“…Worl, 2020), but concern remains that some organs, including the lungs, might suffer long-term impairment following recovery from acute infections. Individual studies have shown that residual abnormalities of pulmonary function were observed in a subgroup of recovered COVID-19 patients, with the most common finding being a reduction in gas transfer as measured by diffusing capacity of the lungs for carbon monoxide (DLCO) (Hull et al, 2020;Dhawan et al, 2021;Thomas et al, 2021). In this study, with meta-analysis, we aimed to determine the short (0-3 months), medium (3-6 months) and long (>6 months) respiratory outcomes in patients following COVID-19related hospitalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Worl, 2020), but concern remains that some organs, including the lungs, might suffer long-term impairment following recovery from acute infections. Individual studies have shown that residual abnormalities of pulmonary function were observed in a subgroup of recovered COVID-19 patients, with the most common finding being a reduction in gas transfer as measured by diffusing capacity of the lungs for carbon monoxide (DLCO) (Hull et al, 2020;Dhawan et al, 2021;Thomas et al, 2021). In this study, with meta-analysis, we aimed to determine the short (0-3 months), medium (3-6 months) and long (>6 months) respiratory outcomes in patients following COVID-19related hospitalisation.…”
Section: Introductionmentioning
confidence: 99%
“…More stringent mitigation measures may again be required in the future to control the spread of the disease (9) and such measures will undoubtedly affect the operation of pulmonary function laboratories. Moreover, lung function anomalies and psychological sequelae are not uncommon in individuals recovering from COVID-19 (10,11) which implies that a constantly increasing number of patients will require close lung function monitoring during the pandemic (12). Therefore, guidelines on pulmonary function testing that include specific action plans and may dynamically adapt to sudden epidemiologic changes, are required.…”
Section: Introductionmentioning
confidence: 99%
“…Readily available treatment options for outpatients become more and more important because the spread of highly transmissible variants will likely result in large numbers of patients being quarantined at home with on average younger age and a comparatively mild-to-moderate disease course. This population is not commonly expected to experience severe inflammatory conditions but effective early treatment could reduce and/or prevent morbidity, and future studies should assess whether treatment with ELOM-080 could contribute to preventing the development of long COVID symptoms [ 19 ].…”
Section: Discussionmentioning
confidence: 99%